Stabilization of Pb, Cu, and Zn in Phytoaccumulator Ash in Calcined Clay-based Geopolymers and Potential Application - Ogunsola, Samuel Sunday; Adelodun, Adedeji Adebukola; Ogundiran, Mary Bosede (Tropical Aquatic and Soil Pollution, 2024)
Following phytoremediation, the disposal of accumulating plants (phytoaccumulators) is challenging because the accumulated metals could leach back into the soil if not properly managed. Therefore, this study aims to use calcined clay (CC)-based geopolymer to stabilize Pb, Cu, and Zn in a phytoaccumulator (Sporobolus pyramidalis) ash (PA). Additionally, the effect of adding PA on the setting time, mechanical and heavy metals leaching properties of the geopolymers was investigated, to determine their environmental suitability and potential applications. Mixed proportions of CC (85-100%) and PA (5% - 15%) were used to produce geopolymers, using 8 M NaOH/Na2SiO3 (1:1) as an alkaline activator. The geopolymers were cured for 7 and 28 days at ambient temperatures. Thermograms showed the dehydroxylation of kaolinite at 450-650 °C. X-ray flourescene (XRF) analysis showed CC’s predominant oxides as SiO2 (53.1%) and Al2O3 (41.4%), while PA exhibited SiO2 (46.6%), CaO (13.8%), PbO (1.30%), ZnO (0.28%), and CuO (0.04%). Thermal treatment eliminated most FTIR bands associated with kaolinite, converting crystalline kaolinite into amorphous metakaolinite. Geopolymer setting time ranged from 75 min (100% CC) to 111 min (85% CC). Furthermore, elevated Cao content in the PA resulted in the geopolymer’s early strength development. However, the compressive strength decreased as PA quantity increased, with 95% CC-PA exhibiting maximum strength (22.5 ± 0.2 MPa) after 28 days. Further tests confirmed that 95% and 90% CC-PA geopolymer effectively stabilized Pb and Cu. Fabricated geopolymers met the ASTM (C62-17) Specification Standard for building brick, indicating their suitability as a waste-based construction material under controlled conditions.